TSEN54 Gene-Related Pontocerebellar Hypoplasia Type 2 Could Mimic Dyskinetic Cerebral Palsy with Severe Psychomotor Retardation - Pacheva, Iliyana Hristova; Todorov, Tihomir; Ivanov, Ivan; Tartova, Desislava; Gaberova, Katerina; Todorova, Albena; Dimitrova, Diana (Frontiers in Pediatrics, 2018)
Pontocerebellar hypoplasia (PCH) type 2 is a very rare autosomal recessive neurodegenerative disorder with prenatal onset that disrupts brain development. We present three patients (two siblings and one unrelated child) with PCH 2 linked to the most common mutation c.919G>T, (p.Ala307Ser) in TSEN54 gene. The disease started soon after birth with feeding difficulties, extrapyramidal symptoms, psychomotor retardation, progressive microcephaly. Two of the patients were diagnosed with dyskinetic cerebral palsy at first. Despite the neurodegenerative character of PCH 2, the absence of regression and even some developmental progress in few patients, might erroneously lead to the incorrect diagnosis of dyskinetic cerebral palsy. Megacisterna magna on brain ultrasound makes the diagnosis of PCH 2 highly probable and should prompt further imaging with MRI. MRI findings of pontocerebellar hypoplasia are pivotal for the diagnosis. Genetic testing for the most common mutation in TSEN54 gene should also be performed. Correct diagnosis of PCH 2 is essential not only for the prognosis of the patient, but also for prenatal diagnosis in future pregnancies. Knowledge of the clinical picture of PCH 2 will lead to correct and timely diagnosis. Advanced neuroimaging procedures and molecular genetic techniques provide valuable tools for prompt diagnosis of rare, but clinically important, neurogenetic imitators of cerebral palsy.